2023
DOI: 10.3390/buildings13010185
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultra-High-Performance Concrete in Bridge Engineering: Current Status, Limitations, Challenges, and Future Prospects

Abstract: Ultra-high-performance concrete (UHPC) is a form of cementitious composite that has been the most innovative product in concrete technology over the last three decades. Ultra-high-performance concrete has been broadly employed for the design of numerous forms of construction owing to its excellent mechanical characteristics and durability, and studies on its behavior have grown fast in the last decades. While the utilization of ultra-high-performance concrete in bridge engineering (BE) is limited owing to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Sun et al [6], Shi et al [25], Faried et al [30], and El-Din et al [45] have pointed out the importance of the management process of various additions in the mixture of UHPC to obtain efficient mechanical properties with a long lifetime. Such management meets the main challenge of reducing the amounts of cement and steel fibers while clearly enhancing the concrete specifications [15,47,49].…”
Section: Compressive Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al [6], Shi et al [25], Faried et al [30], and El-Din et al [45] have pointed out the importance of the management process of various additions in the mixture of UHPC to obtain efficient mechanical properties with a long lifetime. Such management meets the main challenge of reducing the amounts of cement and steel fibers while clearly enhancing the concrete specifications [15,47,49].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…They indicated that the A-UHPC can provide the highest hardened behavior at a water-binder ratio of 0.27-0.29 and recycled concrete content of 10-30% [46]. Abdal et al [47] studied the main structural factors in UHPC to be used efficiently in applications of bridge engineering and showed their review on the interaction between many construction parameters and their influences on the final product cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high PC volumes generate a considerable quantity of carbon dioxide. Enormous amounts of resources and energy have been used, which led to an increase in the possible environmental repercussions of UHPC on a global scale [23]. Thus, to enable the building industry to be more ecologically and economically sustainable, it is recommended to replace the PC in concrete preparations with various additives and to substitute diverse sources of natural aggregates with recycled aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on concrete materials [9][10][11][12][13][14] has led to a rapid advancement of UHPC in the field of civil engineering, emerging as a new and highly efficient material. UHPC is formulated based on the Danish DSP system, which follows the principle of achieving maximum packing density [15].…”
Section: Introductionmentioning
confidence: 99%